MEASUREMENT OF NATURAL RADIOACTIVITY IN SAND SAMPLES COLLECTED FROM THE BAOJI WEIHE SANDS PARK, CHINA - Xinwei L.; Xiaolan Zh. (My University, 2006)
The activity concentrations and the gamma-absorbed dose rates of the primordial naturally occurring radionuclides 226Ra, 232Th and 40K were determined for sand samples collected from the Baoji Weihe Sands Park, China, using γ-ray spectrometry. The natural radioactivity concentration of sand ranges from 10.2 to 38.3 Bq kg−1 for 226Ra, 27.0 to 48.8 Bq kg−1 for 232Th and 635.8 to 1,126.7 Bq kg−1 for 40K with mean values of 22.1, 39.0 and 859.1 Bq kg−1, respectively. The concentrations of these radionuclides are compared with the typical world values and the average activity of Chinese soil. The measured activity concentration of 226Ra and 232Th in sand is lower than the world average while that of 40K is higher. . To evaluate the radiological hazard of the natural radioactivity, the radium equivalent activity, the external hazard index, the absorbed dose rate, and the effective dose rate have been calculated and compared with internationally approved values. The radium equivalent activity values of all sand samples are lower than the limit of 370 Bq kg−1. The values of the external hazard index are less than unity. The mean outdoor air absorbed dose rate is 69.6 nGy h−1 and the corresponding outdoor effective dose rate is 0.085 mSv y−1.
Keywords: NATURAL RADIOACTIVITY; SAND; γ-RAY SPECTROMETRY; GAMMA DOSE RATE; SANDS PARK; CHINA